METHODOLOGY FOR USING MODERN FORMS AND TOOLS IN THE ORGANIZATION OF INDEPENDENT WORK OF STUDENTS IN AN INFORMED EDUCATIONAL ENVIRONMENT: https://doi.org/10.5281/zenodo.14870208 - Mamurova , Malohat (Journal of Contemporary World Studies, 2025)
In this article, the information educational environment in improving the quality and efficiency of education in the world was determined by the insufficient knowledge of modern information technologies in the form of the effective organization of independent work of students, academic alternatives for students and teachers, innovative educational technologies, and the field of fundamental knowledge. In addition, the credit system in the higher education system and the organization of independent work of students in it, its forms, the current state, and the views of many scientists on the effective organization of independent work of students are covered. Information is provided on the organization of independent work of students at the institute, implementation in a specific subject.